A Comprehensive Study of Wave Angels and their Influence on Sail Boats - Jangka Rulianto; Anggra Fiveriati; IGNB Catra Wedarma (National Research and Innovation Agency (BRIN Publishing), 2023)
Sail boat is a type of sail boat with the main mover in the form of a sail that utilizes the wind to generate thrust so that it can go according to the desired speed. Although the type of sail propulsion has been found since time immemorial, research on sails and their effects on sailboats is very rarely done. In general, research only focuses on calculating the size of the sail so that the sailboat is able to go at the desired speed without considering other things that might happen to the sailboat if the sail is used. Therefore, the researcher intends to analyze the force on the sail with variations of the sail and ring and its effect on the sailboat. Based on the results of the research conducted, taking into account the wind conditions in the coastal area of ​​Banyuwangi, the results of the data analysis are as follows, including the size of the main sailing vessel that is suitable for having a length of 5 meters, a width of 2 meters and a height of 1 meter and a water laden depth of 0 ,5 meters. The best wind direction is at 180° or behind the sail boat. The optimum wind speed that can be used is 30 knots or 15 m/s. And the maximum heeling degree that can be tolerated before the sail boat is 25° Direction of port side and right.